Does Modification of Amalgomer with Propolis Alter Its Physicomechanical Properties? An In Vitro Study - Reham M. Abdallah; Amr M. Abdelghany; Neven S. Aref (International Journal of Biomaterials)
Objective. To assess if incorporating ethanolic extract of propolis into ceramic-reinforced glass ionomer (Amalgomer CR) might have an influence on its physicomechanical properties. Materials and Methods. Three groups were assessed; group I: Amalgomer CR (control) and two experimental groups (II and III) of propolis added to the liquid of Amalgomer CR with 25 and 50 v/v %, respectively. Evaluation parameters were color stability, compressive strength, microhardness, and surface roughness. Representative specimens of each group were analyzed by Fourier-transform infrared spectroscopy, energy-dispersive X-ray, X-ray diffraction, and scanning electron microscopy. Analysis of variance (ANOVA) was used to compare the results, followed by a Tukey post hoc test (p<0.05). Results. Nonsignificant color change for both groups of modified Amalgomer CR. Meanwhile, the two experimental groups exhibited a significant increase in both compressive strength and microhardness. Simultaneously, there was a significant difference in roughness values among groups with the lowest roughness values exhibited by the 50 v/v % propolis concentration. Conclusions. Modification of Amalgomer CR with 50 v/v % propolis may increase its mechanical properties without compromising its esthetic. Clinical Significance. Modification of Amalgomer CR by 50 v/v % propolis is supposed to be a hopeful restorative material with favorable characteristics.